Vpliv dejavnikov tveganja na težave v spolnosti pri moških po petdesetem letu starosti - Habjanič, Ana (Obzornik zdravstvene nege, 2013)
Introduction: Sexual problems can have a negative impact on the quality of life in men aged 50 years or more. Therefore, the identification of risk factors is an important professional concern of primary health care. A literature review on the topic reveals a relative scarcity on sexual dysfunction, but the issue requires additional attention due to the extended longevity. Methods: A cross-sectional research was conducted including men aged 50 years or more who visited a general practitioner in July and August 2012 (n = 105). Convenient and non-random purposive sampling was used. The data gathered by structured questionnaire were statistically analysed. Results: The results of logistic regression showed statistically significant decrease in sexual function in patients with cardiovascular diseases. (OR 6.08, 95% CI 1.96 - 18.82, p = 0.002). Other health problems and unhealthy lifestyle were not confirmed to be associated with sexual problems. Discussion and conclusion: The results of the study in a certain degree corroborate previous research on positive correlation between concurrent health disorders and sexual dysfunction. Associations of unhealthy lifestyle factors with sexual dysfunctions were, however, not established. Although sexual dysfunction falls in the province of medicine, nurses in clinical practice may nonetheless offer counselling and encourage the patients to address and openly discuss the issue.
Keywords: cross-sectional research; dejavniki tveganja; man; men; moški; presečna raziskava; risk factors; sexual disorders; težave v spolnosti